An agent-based simulation model for analyzing the impact of teacher behavior in case of evacuation from daycare classrooms - Ferro Junior, Raimundo J. C.; da Silva, Thayanne F.; Andrade, João P. B.; de Campos, Gustavo A. L. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4456, 2018)
Agent-based simulations can be used to study and formulate evacuation plans, however the traditional simulation models for this context are not suitable for daycare and school settings where the population of these settings has unique physical and behavioral characteristics. This paper proposes a simulation model based on classroom evacuation agents from daycare centers that takes into account the physical and behavioral characteristics of the students and that is able to provide data to evaluate the impact of teachers’ behavior in the evacuation process. The model was built using the Netlogo tool, using as basis the structures of the Brazilian classroom environment and using data from the literature on human behavior. The tests were performed in different settings of parameters for environment, population, student behavior and evacuation strategies. The experiments showed that the model was able to reproduce results consistent with the expected values and scenarios described in the literature, as well as being an effective tool to evaluate the impact of teacher behavior in the evacuation process, especially in rooms where students have a high degree of dependency.